PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN AKTIVITAS BELAJAR, HASIL BELAJAR FISIKA DAN MOTIVASI BELAJAR SISWA SMAN 01 MUKOMUKO - Anita Setya Rahayu; Indra Sakti; Desy Hanisa Putri (UNIB Press, 2017)
This research was classroom action research in term of Work and Energy concept which has been done in four cycles where the purpose was to know the enhancement of students’ learning activities, learning outcomes, and learning motivation. The subjects of this research were all 36 first grade students of science 3 class in senior high school number 01 Mukomuko. The result of this research has shown that the total average of students’ activities in cycle I was 38 with predicate active, in cycle II was 40with predicate active, 41 in cycle III with predicate active, and in cycle IV was 42 with predicate active. Students’outcomes on cognitive aspect in cycle I has shown that the students’ absorbption level was 83,64% and students’ passing criteria was 58,33% (unpassed), has increased in cycle II into 88,11% and learning passing criteria was 80.55% (unpassed), then the level of absorbption increased in cycle III about 92.90% and learning passing criteria was 91.66% (passed) and significantly increased comparing to cycle I, II, and III where in cycle IV the level of absorbption was 97.68% and learning passing criteria was 100%. Learning outcomes in psychomotor aspect in cycle I was 88.34, 91, 58 in cycle II,93,19 in cycle III, and 96,39 in cycle IV. Students’ motivation was 61,06 in cycle I, 60,21 in cycle II, 64,50 in cycle III, and 65,60 in cycle IV. Based on the results of research can be concluded that the application of problem-based learning model can improve learning activities, learning outcomes in Physics and students’ learning motivation.